2020
DOI: 10.4103/jehp.jehp_125_20
|View full text |Cite
|
Sign up to set email alerts
|

Module to facilitate self-directed learning among medical undergraduates: Development and implementation

Abstract: CONTEXT: Currently, self-directed learning (SDL) is emphasized in medical institutions all over the world. The skills of SDL enable one to be a lifelong learner, a necessity to cope up with fast-expanding medical knowledge. AIMS: This study aims to develop and implement an “SDL” module for medical undergraduates and find out their perception about the same. SETTINGS AND DESIGN: A cross-sectional study using a mixed-method design (having both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…Currently, SDL is emphasized in medical institutions all over the world. The skills of SDL enable one to be a lifelong learner, which is a necessity to cope with fast expanding medical knowledge (18).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, SDL is emphasized in medical institutions all over the world. The skills of SDL enable one to be a lifelong learner, which is a necessity to cope with fast expanding medical knowledge (18).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations